1997
DOI: 10.1038/bjc.1997.116
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of docosahexaenoic acid on colon carcinoma 26 metastasis to the lung

Abstract: Summary Unsaturated fatty acids, including n-3 polyunsaturated fatty acids (PUFAs) such as docosahexaenoic acid (C225, DHA) and eicosapentaenoic acid (C20.5, EPA), and a series of n-6 PUFAs were investigated for their anti-tumour and antimetastatic effects in a subcutaneous (s.c.) implanted highly metastatic colon carcinoma 26 (Co 26Lu) model. EPA and DHA exerted significant inhibitory effects on tumour growth at the implantation site and significantly decreased the numbers of lung metastatic nodules. Oleic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
119
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 19 publications
4
119
1
1
Order By: Relevance
“…19,20 Indeed, our histologic examinations of mice bearing CT-26 colon carcinoma of approx. 1,766 mm 3 (15 mm in diameter) revealed metastatic foci in the lungs and livers of these mice.…”
Section: Discussionmentioning
confidence: 93%
“…19,20 Indeed, our histologic examinations of mice bearing CT-26 colon carcinoma of approx. 1,766 mm 3 (15 mm in diameter) revealed metastatic foci in the lungs and livers of these mice.…”
Section: Discussionmentioning
confidence: 93%
“…Increased apoptosis induction of metastatic tumours after DHA treatment was also observed 49 . This activity may be related to changes in the fatty acid composition of tumour cells, which impaired the tumour cell membrane and reduced the ability to metastasize 109 . Moreover, impaired attachment to endothelial cells and the indicated decrease in metalloproteinase-9 activity in tumour cells may play a role in these effects 110 .…”
Section: Antimetastatic and Antiangiogenic Activity Of Dhamentioning
confidence: 99%
“…In our study, the degradation and the absorption ratios of bovine lactoferrin that were applied via oral administration in rabbits were not examined. However, Iigo et al [13] reported that bovine lactoferrin was not detectable in the portal blood of mice given an oral dose of 300 mg/kg bovine lactoferrin, suggesting that the lactoferrin was less likely to be transported from the intestine into the blood thereby interacting with bone-related cells directly when administered orally. We used a dose of 85 mg/kg/day of bovine lactoferrin, according to a previous report [9], however, the actual serum concentrations of bovine lactoferrin were not measured.…”
Section: Discussionmentioning
confidence: 99%